Procreational Desires and Their Realization: A Study of Target Groups with Parents - Ražauskienė, Vilma; Šumskaitė, Lina (Socialinė teorija, empirija, politika ir praktika, 2021)
Scientific research has shown that the procreational intentions and the actual number of children born may not coincide (Lutz 2020; Stankūnienė et al 2013; Testa 2013). Although the most common ideal number of children in European Union is two, not a single country has the total fertility rate of two (Beaujoun ir Sobotka 2014). The aim of current research is, first, to ascertain what procreational desires people have and, second, to shed some light on possible factors that influence the realization of those procreational desires. Three focus group discussions were conducted with parents 26 – 44 years of age (ten participants in total). It was found out that the procreational desires are not static and early determined: they change depending on the circumstances of the family creation, self-realisation in one‘s occupation and the reconciliation of the procreational desires of the partners. In accordance to other studies on the topic of procreational desires and their fulfillment, the results of this study demonstrate that the common obstacles that arise while trying to realize one‘s procreational desires are of social, financial and medical nature. Also, the results show that state support for families may have an impact on the number of children a family has if the family has been enduring some financial difficulties.